Genevieve's war - Giff, Patricia Reilly (Holiday House, 2017)
"In August 1939 Genevieve makes an impulsive decision not to get on train to take her to boat back New York and must spend the duration of World War II with her grandmother in a small village in Alsace, France, where she becomes involved with the French resistance"--